Tannic acid: A sustainable crosslinking agent for high glass transition epoxy materials. Issue 13 (1st July 2018) - Korey, Matthew; Mendis, Gamini P.; Youngblood, Jeffrey P.; Howarter, John A.
ABSTRACT: Epoxy thermosets have revolutionized the coating, adhesive, and composite industries but the chemicals from which they are synthesized have significant effects on the environment and human health not only precure but also after crosslinking has occurred. In this study, we propose tannic acid (TA) as an alternative epoxy hardening agent for commercially available epoxy resin, the diglycidyl ether of bisphenol A (DGEBA). The resulting thermosets were characterized by Fourier transform infrared spectroscopy, optical microscopy, dynamic mechanical analysis, differential scanning calorimetry, compression testing, and thermogravimetric analysis. The results from this study showed that at temperatures above 100 °C, the compatibility of TA in DGEBA was significantly increased for loading levels up to 37% weight of TA in DGEBA, something that has not been seen before in literature. It was also discovered that at high loading levels, the resulting materials had glass transition temperatures at and above 200 °C. The resulting material was proposed as a more sustainable alternative to amine or acid hardened epoxy thermosets and was particularly useful in high‐temperature applications. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1468–1480 Abstract : The chemicals within epoxy thermosets have significant, unintended effects on human health and the environment. Tannic acid is a well known polyphenolic biomolecule found in a variety of trees, seeds, and nuts that is generally regarded as safe and FDA approved for consumption. In this work, tannic acid is studied as a proposed biologically‐sourced, alternative epoxy hardening agent. Resulting thermosets had glass transition temperatures at or above 200 °C, making them high glass transition epoxy thermosets.